Association of Fetomaternal Outcomes of Labour with Eclampsia - Mashoor, Irum; Jadoon, Samina; Jabbar, Nousheen; Niazi, Sundas (Indus Journal of Bioscience Research, 2025)
Background: Eclampsia is a severe complication of hypertensive disorders in pregnancy and remains a significant cause of maternal and neonatal morbidity and mortality. While preeclampsia can be managed with early interventions, the transition to eclampsia leads to life-threatening complications. Objective: The objective of this study was to determine the frequency of adverse fetomaternal outcomes in patients with eclampsia and preeclampsia and to evaluate their association with these hypertensive disorders of pregnancy. Study Design: Descriptive study. Duration and Place of Study: This study was conducted from 01 October 2024 to 15 January 2025 at the Department of Obstetrics and Gynaecology, Mardan Medical Complex, Mardan. Methodology: A total of 100 patients diagnosed with preeclampsia or eclampsia were included. Participants aged 18–40 years with singleton pregnancies beyond 32 weeks of gestation were enrolled. Demographic data, clinical parameters, and fetomaternal outcomes were recorded. The primary outcomes assessed included acute kidney injury, HELLP syndrome, pulmonary edema, maternal mortality, perinatal mortality, and NICU admissions. Results: Among the study participants, acute kidney injury was observed in 24% of cases (70.8% in preeclampsia vs. 29.2% in eclampsia, p=0.685). HELLP syndrome was significantly higher in eclamptic patients (94.1% vs. 5.9%, p<0.001). Pulmonary edema occurred more frequently in eclampsia cases (83.3% vs. 16.7%, p=0.004). Maternal mortality was recorded in 3% of cases (33.3% in preeclampsia vs. 66.7% in eclampsia, p=0.165). Conclusion: Eclampsia poses greater fetomaternal risks than preeclampsia, including HELLP syndrome, pulmonary edema, and perinatal death. High NICU admissions highlight severe neonatal outcomes, underscoring the need for early diagnosis, vigilant monitoring, and timely intervention to improve maternal and neonatal outcomes.